2020
DOI: 10.15252/msb.20198870
|View full text |Cite
|
Sign up to set email alerts
|

Organization at criticality enables processing of time‐varying signals by receptor networks

Abstract: How cells utilize surface receptors for chemoreception is a recurrent question spanning between physics and biology over the past few decades. However, the dynamical mechanism for processing time‐varying signals is still unclear. Using dynamical systems formalism to describe criticality in non‐equilibrium systems, we propose generic principle for temporal information processing through phase space trajectories using dynamic transient memory. In contrast to short‐term memory, dynamic memory generated via “ghost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Necessary for manifestation of the ‘ghost’ state is organization at criticality, before the . We have previously examined both theoretically and experimentally, the response of receptor networks under uniform growth factor stimulation and determined that the concentration of receptors on the cell membrane regulate the organization of the system at criticality ( Stanoev et al, 2018 ; Stanoev et al, 2020 ). The features of both bifurcations, cell polarization under spatial cues and a transient memory of this polarization in absence of the cue, will be unified for a sub-critical , as it is stabilized via s. We thus propose that organization at criticality - in the vicinity of a (gray shaded area in Figure 1—figure supplement 1A ; details discussed in Materials and methods), renders a minimal mechanism for cellular responsiveness in changing environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Necessary for manifestation of the ‘ghost’ state is organization at criticality, before the . We have previously examined both theoretically and experimentally, the response of receptor networks under uniform growth factor stimulation and determined that the concentration of receptors on the cell membrane regulate the organization of the system at criticality ( Stanoev et al, 2018 ; Stanoev et al, 2020 ). The features of both bifurcations, cell polarization under spatial cues and a transient memory of this polarization in absence of the cue, will be unified for a sub-critical , as it is stabilized via s. We thus propose that organization at criticality - in the vicinity of a (gray shaded area in Figure 1—figure supplement 1A ; details discussed in Materials and methods), renders a minimal mechanism for cellular responsiveness in changing environments.…”
Section: Resultsmentioning
confidence: 99%
“…The memory in polarized signaling was also reflected on the level of the cell morphology, as shown by the difference of normalized cell protrusion area in the front and the back of the cell over time ( Figure 1G ). Plotting the trajectory that describes the change of the state of the system over time (state-space trajectory, Figure 1F bottom) shows that the temporal memory in EGFR phosphorylation polarization is established due to transient trapping of the signaling state trajectory in state-space, a property of the metastable ‘ghost’ state ( Stanoev et al, 2020 ; Strogatz, 2018 ) through which the system is maintained away from the steady state. The simulations show that there are two characteristic time-scales present in the system: slow evolution of the system’s dynamics in the ‘ghost’ state due to the trapping, and fast transitions between the steady states ( Figure 1—video 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work we identified that when a saddle-node bifurcation ( SN ) and thereby a steady-state is lost in a dynamical transition, i.e. upon signal removal, a remnant or a dynamical ”ghost” of the stable attractor serves as a mechanism for sensing timevarying growth factors in biochemical receptor networks (Stanoev et al, 2018; Stanoev et al, 2020). Necessary for manifestation of the ”ghost” state is organization at criticality, which in the networks we previously examined was determined by the concentration of receptors on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Plotting the trajectory that describes the change of the state of the system over time (state-space trajectory, Figure 1F bottom, movie S1) shows that the temporal memory in EGFR phosphorylation polarization is established due to transient trapping of the signaling state trajectory in state-space. This is typical for the emergence of metastable "ghost" states (Stanoev et al, 2020;Strogatz, 2018), indicating that the system is maintained away from steady-states. The trapping in the dynamically-metastable memory state does not hinder sensing of and adapting to subsequent signals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation